Visualising an Academic Institution's Image Through Brand Mascots: Pradita University - Tjhie, Beatrice Wiguna; Sekarasri, Andreana Lingga; Gunawan, Ardi Makki Pantow (Universitas Multimedia Nusantara, 2023)
A student’s choice of an academic institution is influenced by the reputation and public perception of the university; these factors are often shaped by brand awareness. As Pradita University is a recently established institution, it is essential to increase its brand awareness and image to facilitate a positive perception among prospective students. The researchers have proposed that the utilization of brand mascots could serve as a strategy to increase brand awareness as existing studies have highlighted the advantages of brand mascots in this regard, albeit not in the context of academic institutions. This research will discuss the feasibility and effectiveness of incorporating a brand mascot to increase brand awareness and image within an academic institution while delving into design elements that contribute to a memorable mascot. The outcome of this research is a mascot that is expected to increase brand awareness and image through market implementation and interaction. Future research could further explore the long-term effectiveness and influence of brand mascots on brand awareness.